Dampak Krisis Ekonomi dan Angkutan Umum Perkotaan - BS Kusbiantoro (The Institute for Research and Community Services, Institut Teknologi Bandung, 1999)
Economic crisis has created negative effects on users, owners, and drivers of urban public transit system. To analyze the impacts, a study was conducted for urban public transit system in Bandung. Respondents were asked various questions related to travel and other expences before and after the crisis. The results showed how the low income users were affected the most. They were captive users and had to sacrifice their meal expenses for transportation costs. The public transit's drivers and owners were affected by the crisis as well, mostly by the increasing operational cost and spareparts. Some recommendations are presented to deal with these problems.